Quality of Pharmacological Services at Jasem Sidoarjo General Hospital - Prima Dewi Kusumawati; Adani Dinanhashfi Hersariti; Ajeng Rahardyani Hersariti; Ardilla Oktaviana (Journal of Community Engagement in Health, 2024)
Pharmaceutical service is a direct service that is responsible for patients regarding pharmaceutical preparations to achieve definite results in order to improve the patient's quality of life. Pharmacists must understand and be aware of the possibility of errors occurring in the service process and even in medication (medication errors). Medication errors are events that cause harm to patients due to the use of medication while being treated by health workers that could have been prevented. Therefore, pharmacists in carrying out their practices must comply with existing standards to avoid this happening. Pharmacists must be able to communicate with other health professionals in determining therapy to support rational drug use. In the residency assignment, the author has written about various strengths, weaknesses, opportunities and threats to the quality of pharmacological services at the Jasem Sidoarjo General Hospital. In this study there are several strategies to improve the handling of health services for pregnant women and toddlers. Based on the conditions above, the author wants to implement a strategy to improve the quality of pharmacological services at the Jasem Sidoarjo General Hospital. This activity begins by collecting data on drugs that run out quickly and those that are slow, as well as creating a return/compensation system for unused drugs, and recommending to management to spend the majority of the budget to replenish drug stocks at the pharmacy depot to make things easier for patients. Create standard operating procedures down to every little thing and distribute them to every room, even to the pharmacy depot. Updating the integrated computer system using the latest SIM-RS to synchronize data. Conduct training for all employees in stages. And evaluate patient satisfaction once a month. It is hoped that health workers will routinely supervise and monitor the reliability and ability of staff in the quality of pharmacological services at the Jasem Sidoarjo General Hospital so that the quality of service at the hospital can be sustainable and increase patient satisfaction.